Understanding human fetal pancreas development using subpopulation sorting, RNA sequencing and single-cell profiling - Ramond, C; Beydag-Tasöz, BS; Azad, A; van de Bunt, M; Petersen, MBK; Beer, NL; Glaser, N; Berthault, C; Gloyn, AL; Hansson, M; McCarthy, M; Honoré, C; et al. (Company of Biologists, 2018)
To decipher the populations of cells present in the human fetal pancreas and their lineage relationships, we developed strategies to isolate pancreatic progenitors, endocrine progenitors and endocrine cells. Transcriptome analysis of the individual populations revealed a large degree of conservation among vertebrates in the drivers of gene expression changes that occur at different steps of differentiation, although notably, sometimes, different members of the same gene family are expressed. The transcriptome analysis establishes a resource to identify novel genes and pathways involved in human pancreas development. Single-cell profiling further captured intermediate stages of differentiation and enabled us to decipher the sequence of transcriptional events occurring during human endocrine differentiation. Furthermore, we evaluate how well individual pancreatic cells derived in vitro from human pluripotent stem cells mirror the natural process occurring in human fetuses. This comparison uncovers a few differences at the progenitor steps, a convergence at the steps of endocrine induction, and the current inability to fully resolve endocrine cell subtypes in vitro.